2023
DOI: 10.3389/fnmol.2023.1133271
|View full text |Cite
|
Sign up to set email alerts
|

Implications of specific lysine residues within ataxin-3 for the molecular pathogenesis of Machado-Joseph disease

Abstract: Lysine residues are one of the main sites for posttranslational modifications of proteins, and lysine ubiquitination of the Machado-Joseph disease protein ataxin-3 is implicated in its cellular function and polyglutamine expansion-dependent toxicity. Despite previously undertaken efforts, the individual roles of specific lysine residues of the ataxin-3 sequence are not entirely understood and demand further analysis. By retaining single lysine residues of otherwise lysine-free wild-type and polyglutamine-expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…As the K8 residue is located in close proximity to the critical C14 residue of the catalytic Josephin domain, it has also been suggested that enhanced ubiquitination at this site may impact polyQ-expanded ataxin-3's DUB function [ 77 ]. Ubiquitination of ataxin-3 at the K8 residue has also been suggested by a recent study [ 107 ].…”
Section: Ubiquitination Of Ataxin-3 May Regulate Its Dub Functionmentioning
confidence: 60%
See 2 more Smart Citations
“…As the K8 residue is located in close proximity to the critical C14 residue of the catalytic Josephin domain, it has also been suggested that enhanced ubiquitination at this site may impact polyQ-expanded ataxin-3's DUB function [ 77 ]. Ubiquitination of ataxin-3 at the K8 residue has also been suggested by a recent study [ 107 ].…”
Section: Ubiquitination Of Ataxin-3 May Regulate Its Dub Functionmentioning
confidence: 60%
“…Ataxin-3's UIMs therefore appear to be critical to its DUB function. In support of this, the K85 residue (located between ubiquitin-binding sites 1 and 2) is important for ataxin-3's binding and processing of K48-linked polyubiquitin chains [ 107 ] through the previously described mechanism involving the UIMs and site 2 [ 108 ]. K85 is also important for cytoplasmic localisation of ataxin-3 [ 107 ].…”
Section: Ataxin-3 Functions As a Dub Enzymementioning
confidence: 94%
See 1 more Smart Citation